Values-based Learning: A Multi-Level Approach to Ethical Leadership Development - Dayaram, Kantha; Issa, Theodora (Common Ground Publishing, 2014)
The paper aims to provide empirical evidence towards the ongoing research and debate on the nature of motivation and values that might impact ethical leadership. This paper presents the outcomes of a study that examines the relationship between personal values, consistency of actions and ethical leadership development, using cross-sectional, longitudinal data from a leadership course. Data were collected from 32 postgraduate students at the beginning and end of the semester, testing for pre- and post-leadership intervention effects. In the pre-test, values such as integrity, honesty, trust, self-confidence and transparency were evident. Interventions, including personal reflection, formative learning and action research, had their impact on the way participants thought of ethical leadership, values and personal motivations. The results indicate that particular values that evolved post-test included trust, respect, integrity, self-awareness and responsibility, with empathy, honesty, respect, vision and responsibility remaining consistent throughout the study. These results are in contrast to some prior research in this area, including personal values, leader’s actions and organizational values congruence. Our findings argue that multi-perspective, scaffolded learning is associated with significant levels of leadership reflection and self-awareness. Leaders with higher levels of reflection and self-awareness have significantly higher levels of motivation towards ethical behaviours that are generated from values.